Implementasi Metode Performance untuk Aplikasi Pemesanan Jasa Paket Dokumentasi (Studi Kasus : Quill Photo) - Safila Marina Ramadhani; Adelia Adelia (Jurnal Teknik Informatika dan Sistem Informasi, 2017)
Quill Photo is a private business that offers photography services which still has many obstacles. Customers could only book the documentation service manually, by cell phone (to call or send a short text message to the institution). Administrator have constraints in data processing where the process is still done manually. Human Resources Development (HRD) experienced difficulty in confirming the schedule to the administrator, showing the photos to the customer, and determining the fastest performance of crew. The Logistics Section has a difficult thingto ship the photos. The execution of sending photos ineffective and inefficient when the number of the photos to be sent over quota. Therefore, the web-based application built with one method approach to Performance is expected to facilitate all users to perform activities relating to Quill Photo easily, especially for HRD which is in scheduling photo sessions and measuring the fastest performance of crew.